Protective role of intraperitoneally administered vitamin E and selenium on the antioxidative defense mechanisms in rats with diabetes induced by streptozotocin - Naziroglu, M; Çay, M (Springernature, 2001)
The aim of this work was to determine the protective effects of intraperitoneally administered Vitamin E and selenium (as Na2SeO3, Se) on the lipid peroxidation as thiobarbituric acid reactive substances (TBARS) and vitamin E levels, glutathione peroxidase (GSH-Px), reduced glutathione (GSH) activities in the plasma, red blood cell (RBC), liver, and muscle of rats with streptozotocin-induced diabetes. Fifty adult male Wistar rats were used and all rats were randomly divided into five groups. The first group was used as a control and the second group as a diabetic control. A placebo was given to first and second groups by injection. The third group was intraperitoneally administered with vitamin E (20 mg over 24 h), the fourth group with Se (0.3 mg over 24 h), and the fifth group with vitamin E and Se combination (COM) (20 mg vitamin E + 0.3 mg Se over 24 h). This administration was done for 25 days and the TEARS, vitamin E, GSH-Px, GSH levels in the plasma, RBC, liver, and muscle samples were determined. The vitamin E level in the plasma and liver was significantly (p < 0.05) higher in the control than in the diabetic control group. Also, the TEARS levels in the RBC, liver, and muscle were significantly (p < 0.05) lower in the control than in the diabetic control group. However, GSH-Px and GSH activities in RBC, liver, and muscle were not statistically different between the control and the diabetic control groups. The vitamin E levels in plasma and liver (p < 0.01 and p < 0.001) and GSH-Px activities (p < 0.01, p < 0.001) in RBC were significantly higher in vitamin E, Se, and COM groups than in both control and diabetic control groups. However, the TEARS levels of RBC, muscle, and liver in vitamin E and Se administered groups were significantly (p < 0.05-p < 0.001, respectively) decreased. These results indicate that intraperitoneally administered vitamin E and Se have significant protective effects on the blood, liver, and muscle against oxidative damage of diabetes.
Keywords: selenium; vitamin E; diabetes; lipid peroxidation; liver